Environmental Conservation-Based Sustainable Tourism at Mount Baung Nature Tourism Park, Indonesia - Joyti, Joyti; Satti Wagistina (Jurnal Pembangunan dan Alam Lestari, 2023)
Mount Baung Natural Tourism Park (MBNTP) is a nature conservation area located in the upstream region of the Pasuruan Regency. MBNTP has interesting biodiversity and natural landscapes that need to be preserved. The aims of this research are: 1) to analyze the function of the MBNTP as a tourism and conservation area, and 2) to analyze the tourist attraction that is by the function of the conservation area. This study uses a quantitative approach and the technique of taking the number of samples by means of quoting. This type of research is observational. The type of data used is primary data collected through observation, interviews, and documentation. Documentation to collect secondary data. The analytical method used is modified indicators ADO-ODTWA (Object Operational Area Analysis of Natural Tourism Parks) and AHP (Analytical Hierarchy Process) which aim to analyze tourism and conservation activities and the influence of area designation in developing the beauty of bird tourism. A study on modifications of ADO-ODTWA and AHP found that MBNTP is consistent in maintaining and controlling the function of the area as a conservation and tourism activity, not as a main activity. The results of the study also show that the attractions that are in accordance with the function of the area are bird watching. However, most bird species in the MBNTP area are not protected and only 4 (four) species have protected status. Because most tourists have an interest in the uniqueness of birds that are classified as rare, birdwatching is more suitable to be combined in one package with outbound tours. Keywords: sustainable tourism; environmental conservation; and tourist attractions